THE DEVELOPMENT RESEARCH OF THE FISHING BOAT DISTINCTION TECHNIQUE BY SATELLITE-ONBOARD HIGH RESOLUTION OPTICAL SENSOR — DISTINCTION TECHNIQUE USING IKONOS DATA - - T. MORIYAMA; - H. TAMEISHI; - J. SUWA; - S. KANNO; - Y. SUGIMORI; - T. OSAWA; - M. KOIWA (National Institute of Aeronautics and Space of Indonesia (LAPAN), 2004)
This paper describes the vessel distinction algorithm by using radiance silhoutte algorithm for IKONOS data. Although original TKONOS image has high spatial resolution about 1 m, it is difficult to identify whole feature of the vessel. The newly developed algorithm named